Effect of Molarity on the Structure, Optical Properties, and Surface Morphology of (002)-Oriented Ni2O3 Thin Films Deposited via Spray Pyrolysis: Effect of Molarity on the Properties of Ni2O3 Thin Films - Aftab, Muzamil; Butt, Muhammad Zakria; Ali, Dilawar; Tanveer, Muhammad Usman; Hussnain, Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Ni2O3 thin films with seven molar concentrations in the range 0.01 – 0.5 M were deposited on pre-heated glass substrates employing spray pyrolysis technique. Structure of the films was (002) oriented hexagonal. The peak intensity and crystallite size increased exponentially with the increase in molarity. Both uniform and non-uniform lattice strains as well as stacking fault probability decreased linearly on increasing molarity. Average values of optical absorbance (0.554 – 0.762), extinction coefficient (0.285 – 0.391), and optical conductivity (2.43 – 3.02) in the visible region (λ = 380 – 740 nm) increased rapidly with molarity in the low molarity range 0.01 – 0.05M and rather slowly in the high molarity range (0.1 – 0.5 M). Both direct (3.99 – 4.045 eV) and indirect (3.37 – 3.52 eV) band gaps decreased whereas Urbach energy (0.33 – 0.42 eV) increased on increasing molarity. Optical reflectance of the films (λ = 270 – 900 nm) was less than 10%. Average reflectance (4.677 – 5.774 %) in the visible region (λ = 380 – 740 nm) decreased linearly on increasing molarity. The average refractive index (1.33 – 1.53) in the visible region decreased linearly with increase in molarity. Surface morphology of the films consisted of random shape nanoparticles. Average surface roughness of the films (0.173 – 0.366 μm) increased rapidly with molarity in the range 0.01 – 0.03 M, and then decreased to an intermediate level (0.284 μm) around which it undulated in the range 0.05 – 0.5 M. Surface roughness of the films strongly exerted its influence on the absorbance, extinction coefficient, and optical conductivity of the films.